From the ground up: Impacts of a pro-poor community-driven development project in Nigeria - Nkonya, Ephraim M.; Phillip, Dayo; Mogues, Tewodaj; Pender, John L.; Kato, Edward (International Food Policy Research Institute, 2010)
The community-driven development (CDD) approach has become increasingly popular because of its potential to develop projects that are sustainable, are responsive to local priorities, empower communities, and more effectively target poor and vulnerable groups. The purpose of this study is to assess the impacts of Fadama II, which is a CDD project and the largest agricultural project in Nigeria. This study used propensity score matching (PSM) to select 1,728 comparable project beneficiaries and nonbeneficiaries. The study also used double difference methods to compare the impact indicators.